2018
DOI: 10.29244/jpsl.8.2.264-270
|View full text |Cite
|
Sign up to set email alerts
|

Studi Etnobotani Tumbuhan Pangan Yang Tidak Dibudidayakan Oleh Masyarakat Lokal Sub-Etnis Batak Toba, Di Desa Peadungdung Sumatera Utara, Indonesia

Abstract: Elephant dung is a source of methane gas, which the gas is the main contributor to greenhouse gas if not used as fuel. Wild elephants use grass leaves as their feed, but in Ragunan Wildlife Park, elephants are fed also with a combination of elephant grass, sweet potatoes, maize, and bananas, which aim to meet immediate nutritional needs and ensure their health. Therefore, this study examined the biogas production of elephant feces associated with the feed given. The purpose of this study is to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 6 publications
0
16
0
16
Order By: Relevance
“…A recent study in a Mandailing community in North Sumatra showed that 106 food plant species are being used, including wild and cultivated ones [ 57 ]. Further in North Sumatra, Batak Toba people from Peadungdung village were found to use 44 species [ 58 ]. Towards the east of Indonesia, only 22 WFPs species were found to be used in Sasak cuisine on Lombok island [ 59 ], while in Bali, 86 species are used [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a Mandailing community in North Sumatra showed that 106 food plant species are being used, including wild and cultivated ones [ 57 ]. Further in North Sumatra, Batak Toba people from Peadungdung village were found to use 44 species [ 58 ]. Towards the east of Indonesia, only 22 WFPs species were found to be used in Sasak cuisine on Lombok island [ 59 ], while in Bali, 86 species are used [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…as an alternative source of alternative carbohydrates (Silalahi et al 2021). The availability of wild food plants is very diverse in the environment, but it is often not liked because it is not tasty and its availability is uncertain (Silalahi et al 2018), even though wild plants are healthier (Pawera et al 2020, Silalahi et al 2021. Utilization and processing of local community food is degraded due to factors such as the entry of information/technology, the presence of modern food (Sujarwo et al 2014), food ingredients are difficult to find (Abbasi et al 2013, Purba et al 2018, information on nutritional value is lacking (Pawera et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Teklehaymanot & Giday, (2010) stated that wild plants can be used as food sources, especially in unfavorable environmental conditions. The wild plants as food ingredients are diverse, but it often disliked because of their bad taste and uncertain availability (Silalahi et al, 2018), even though wild plants are considered healthier (Pawera et al, 2020). Wild plants which can be eaten as food and medicines are threatened with disappearing (Abbasi et al, 2013), therefore it is necessary to conduct various studies to prevent loss of germplasm.…”
Section: Citationmentioning
confidence: 99%